THE INFLUENCE OF TAX BURDEN, TUNNELLING INCENTIVE, AND EXCHANGE RATE ON TRANSFER PRICING - Napitupulu, Ilham Hidayah; Sibarani, Pirma; Gultom, Reni (Kajian Akuntansi, 2024)
This research aims to discover the influence of tax burden, tunneling incentives, and exchange rates on transfer pricing. Transfer pricing deviations can arise in companies that want high profits and avoid taxes in one way. An ownership structure influences the company's decision to carry out transfer pricing and transfer wealth to themselves or the majority shareholder. Companies also use exchange rates to profit by transferring funds into strong currencies. The research uses 37 samples, which are analyzed by multiple linear regression analysis through SPSS tools. The results show that the tax burden and exchange rate do not influence the company's decision to carry out transfer pricing. Meanwhile, tunneling incentives affect transfer pricing.               Keywords     : Exchange Rate, Tax Burden, Transfer Pricing, Tunneling Incentive.